Prevalence and survival of patients with nasopharyngeal malignancies (C11) (clinical and population-based study) - V. M. Merabishvili; Z. A.‑G. Radzhabova; A. B. Vasil’ev; A. L. Popova; M. A. Radzhabova; D. A. Chuglova; A. S. Mitrofanov (Опухоли головы и шеи)
Introduction. In the 10th revision of the International Classification of Diseases (ICD-10), the code for malignant neoplasms of pharynx (mNN) is C11. These tumors are rare. The state statistics only presents information on morbidity. Data on mortality due to mNN are absent, they are included into the group of other causes of death. The real assessment of the effectiveness of antitumor management of mNN can only be obtained from the population Cancer Registry Database (pCR DB) of the Northwestern federal District of the Russian federation (NwfD Rf) developed by us. This database allows to determine the main analytical values of any parameter included in the case report form. The most reliable criterion of evaluation of the effectiveness of antitumor management is calculation of observed and relative 1-year and corrected 5-year survival rates of patients at the population level and in accordance with international standards.Aim. To perform first in Russia assessment of the effectiveness of antitumor management of mNN with calculation of analytical values including survival (separately for men and women) and detailed characteristics of location and histological structure.Materials and methods. The data of the International Agency for Research on Cancer (IARC), as well as reference books of the p.A. Hertsen moscow Oncology Research Institute and the N.N. petrov National medical Research Center for Oncology were used. Data processing was preformed using mS Excel 2013–2016 and STATISTICA 6.1 licensed software. Survival rates were calculated using modified EuROCARE software. The study was based on the databases of the population cancer registry of Saint petersburg and NwfD Rf developed by us. In total, 950 observations were analyzed. Results. Data obtained during investigation of the incidence and survival rates of mNN confirmed the rarity of this pathology and positive morbidity dynamics, standardized values of which decreased in Russia between 2010 and 2022 by 19.35 %, in NwfD Rf by 27.59 %. The coronavirus pandemic had a significant negative effect on the record keeping. Additionally, between 2010 and 2022 1-year survival of patients with mNN in NwfD Rf increased from 58.5 to 80.6 % (by 22.1 %); 5-year survival increased between 2000 and 2018 from 25.4 to 35.4 % (by 10 %).Conclusion. Analysis of the incidence and survival of patients with malignant neoplasm of rare location can be performed only using a database of population cancer registry of a federal district in compliance with all international rules of its maintenance. unfortunately, currently this is possible only for NwfD Rf.